치과진료 장애와 전신건강의 관계에 대한 구강건강의 매개효과와 자기효능감의 조절효과 - 엄숙(Suk Eom); 최유진(Yu-Jin Choi) (한국구강보건과학회지, 2019)
Objectives: This study analyzes the effect of dental disease recognized by individuals on systemic health by mediating oral health. The control effect of self-efficacy, which is a psychological factor of individuals, is likewise examined. On the basis of this study, we will prepare basic data on the various interventions that should be provided for individuals to improve overall health. Methods: In this study, persons who understood the research purpose and agreed to participate were selected as the study target for adults in Busan, Gyeongnam, and Ulsan, and 240 people were used in the analysis. Data collection was conducted from May 22, 2019 to June 10, 2019. Results: The average dental disability, oral health, self-efficacy, systemic health, and dental health disorders of the study subjects scored 3.08, 3.79, 3.73, 3.09, and 3.09 points, respectively (r=−.41, p<.00). Systemic health (r=−27, p<.00) was found to have a correlation between oral health and systemic health (r=.44, p<.001). In the relationship between dental and systemic health, the role of oral health was found to be complete intermediation. In both the high and low oral health-related self-efficacy tests, systemic health was low when dental health was high. In the case of low dental disorders, self-efficacy groups were found to be higher than those with low self-efficacy. Conclusions: It is believed that by developing oral health education and mediation programs, it is necessary to reduce dental health disorder by enhancing oral health related self-efficacy, and to form living habits and behaviors of health promotion activities to promote systemic health as well as oral health. KCI Citation Count: 3